Pediatric Bladder Stone in Secondary Hospital Care Setting: A Case Report - Hafizh Fanani Rizkyansyah; Yudi Y Ambeng (Publikasi Indonesia, 2021)
Bladder Stone is a rare disease accounting for 5% of all urinary calculi. It more common in middle and low-income countries due to nutritional obstacles, water sanitation, and warm climates. Prompt diagnosis and management of pediatric bladder stones are essential for preventing recurrence stones and improving quality of life. It has several surgical approaches. The objective is reporting a child with a bladder stone that came to secondary hospital setting and the best management based on it. This report is qualitative observational study. Material came from direct interview and from medical record. The stone successfully managed with open cystolithotomy.